Reframing Academic Autonomy in Algorithmically Mediated Knowledge Environments - Anwar Alhenshiri; Wesam Elturjman; Hoda Badesh (African Journal of Advanced Pure and Applied Sciences, 2026)
The increasing integration of intelligent recommendation systems into academic research environments represents a fundamental shift in how scholarly knowledge is accessed, evaluated, and produced. While such systems promise efficiency and improved information discovery, their growing influence raises critical theoretical questions concerning academic autonomy, epistemic agency, and algorithmic mediation. This study presents a conceptual and analytical examination of how intelligent recommendation systems interact with the autonomy of research decision-making among academics. Drawing on interdisciplinary literature from artificial intelligence, information science, decision theory, epistemology, and science and technology studies, the study argues that recommendation systems function not merely as neutral tools, but as epistemic mediators that actively structure research choices. Through a comparative analysis of theoretical models, the study demonstrates that academic autonomy is neither simply preserved nor undermined, but reconfigured within algorithmically mediated knowledge environments. The findings contribute a refined theoretical framework for understanding autonomy under algorithmic influence and provide a foundation for future empirical research and ethical system design in academic contexts.